The Nexus of Export, FDI, Financial Development and Economic Growth in North Sumatra, Indonesia - Tampubolon, Jongkers; Nababan, Tongam Sihol; Loh, Aaron (Integrated Journal of Business and Economics (IJBE), 2021)
This study investigated the relationship between exports, foreign direct investment (FDI), financial development and economic growth in North Sumatra, Indonesia. Using autoregressive distributed lag (ARDL) bound test to cointegration, this study confirms the pattern of relationships between economic growth, exports, FDI and financial sector development as follows: (i) FDI does not contribute to the economy of North Sumatra because it does not affect economic growth, exports, and financial development and vice versa, (ii) the causality relationship between economic growth and exports is one way in the pattern of a growth-led export hypothesis (GLEH), and (iii) the causality relationship between financial development and economic growth follows the finance-led growth /supply-leading hypothesis. These findings suggest that the local governments should pay more attention to financial development's crucial role by facilitating the financial sector to expand the banking network and support rural credit banks.